Habitat use of Bechstein´s bats (Myotis bechsteinii) within wind parks in forests - Johanna Hurst; Fränzi Korner-Nievergelt; Robert Brinkmann (PLoS ONE, 2026)
Wind parks are increasingly installed at forest sites, which are a sensitive habitat for bats. As a consequence forest habitats are disturbed and altered by logging, edge effects and turbine operation noises. The Bechstein´s bat ( Myotis bechsteinii ) is highly dependent on forest habitats for roosting and foraging. We analysed the habitat use of breeding colonies of Bechstein’s bats in two wind parks. Over four years, we radio-tracked 31 individuals and identified their maternity roosts and foraging areas. We analysed the influence of the turbines on their habitat use, and the effect of wind speed and rotor blade rotation on the distance of the bats to the turbines. The colonies occupied tree roosts, a few hundred meters from the wind turbines. Foraging habitats close to the turbines were used preferably, when bats were close to the maternity roosts. The vegetation in these areas comprised of large trees and little shrub and herb layer coverage, indicating a high quality foraging habitat. The distance of the foraging bats to the turbines increased with increasing rotor blade rotation at high wind speeds. The results show that Bechstein´s bats become more selective in their habitat use, the closer they are to the wind turbines. Close to their maternity roosts, the advantages of a high quality habitat outweighed the disturbance effects and bats still used roosts and surrounding foraging habitats, despite turbine presence nearby. However, when further away from their roosts they avoided foraging close to wind turbines. With careful site planning, which excludes sensitive forest habitats, combined with restricted turbine operation times in summer, the negative effects of disturbances from wind turbines could be mitigated or avoided for maternity colonies of Bechstein’s bats.